Evaluate
n → ∞ lim k = 1 ∑ n sin ( n 2 + k π ) .
Give your answer to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Mark Hennings , we really liked your comment, and have converted it into a solution. If you subscribe to this solution, you will receive notifications about future comments.
Using Taylor series for sine, we have:
n → ∞ lim k = 1 ∑ n sin ( n 2 + k π ) = n → ∞ lim k = 1 ∑ n [ ( n 2 + k π ) − 3 ! 1 ( n 2 + k π ) 3 + 5 ! 1 ( n 2 + k π ) 5 − . . . ] = n → ∞ lim k = 1 ∑ n n 2 + k π As n 2 + k π → 0 , later terms are negligible (see Note). = k = 1 ∑ n n π = n × n π = π ≈ 3 . 1 4 2
Note:
As n 2 + k π → 0 ⇒ n 2 + k π ≫ ( n 2 + k π ) 3 ≫ ( n 2 + k π ) 5 ≫ . . .
This is not correct. If the later terms are negligible, why can't the first term be negligible as well?
The correct way to solve this is by Squeeze Theorem (Title is a huge spoiler). We should start with
n 2 + 1 ≤ n 2 + k ≤ n 2 + n .
Log in to reply
Exactly! The solution needs to justify that the sum of the latter terms indeed goes to 0 as n → ∞ (this is not obvious). Also, the approximations used in the posted solution are too informal (hand-wavy argument). A formal (rigorous) solution would be given by applying squeeze theorem to the terms of the Maclaurin series expansion of the general term of the series.
Log in to reply
[This comment has been converted into a solution]
At most when k → n , n ( n + 1 ) n = 1 + n 1 ) 1 = 1 as n → ∞ .
n → ∞ lim k = 1 ∑ n sin ( n 2 + n + 0 . 2 5 π ) < n → ∞ lim k = 1 ∑ n sin ( n 2 + k π ) < n → ∞ lim k = 1 ∑ n sin ( n 2 + 0 π )
n → ∞ lim n sin ( n + 0 . 5 π ) < n → ∞ lim k = 1 ∑ n sin ( n 2 + k π ) < n → ∞ lim n sin ( n π )
The left limit:
n → ∞ lim n sin ( n + 0 . 5 π ) = n → ∞ lim ⎝ ⎛ n + 0 . 5 π sin ( n + 0 . 5 π ) ⎠ ⎞ ( n + 0 . 5 n ) ( π ) = 1 × 1 × π = π
The right limit:
n → ∞ lim n sin ( n π ) = n → ∞ lim ⎝ ⎛ n π sin ( n π ) ⎠ ⎞ ( π ) = 1 × π = π
The limit is π by the Squeeze theorem.
Problem Loading...
Note Loading...
Set Loading...
Using the inequality ∣ sin x − x ∣ ≤ 6 1 x 3 for 0 ≤ x ≤ 1 , we see that ∣ ∣ ∣ ∣ ∣ k = 1 ∑ n sin ( n 2 + k π ) − k = 1 ∑ n n 2 + k π ∣ ∣ ∣ ∣ ∣ ≤ k = 1 ∑ n 6 ( n 2 + k ) 2 3 π 3 ≤ 6 n 2 π 3 , for n ≥ 3 , and so we want to evaluate S = n → ∞ lim k = 1 ∑ n sin ( n 2 + k π ) = n → ∞ lim π k = 1 ∑ n n 2 + k 1 . Now n + 1 n = n 2 + n n ≤ k = 1 ∑ n n 2 + k 1 ≤ n 2 + 1 n < 1 Since n + 1 n converges to 1 as n → ∞ , the Squeeze Theorem can now be applied to give S = π .
It is always risky to discard a limit of a sum of an infinite number of terms just because the limit of each term is zero, just in case the sum of those terms does not converge to zero.